2015
DOI: 10.1037/aap0000016
|View full text |Cite
|
Sign up to set email alerts
|

Korean American adolescent ethnic-identity pride and psychological adjustment: Moderating effects of parental support and school environment.

Abstract: Researchers have consistently reported positive relationships between psychological adjustment and ethnic identity or related elements such as ethnic-identity pride. However, few efforts have been made to determine whether such links are context-dependent. Here we apply person-environment fit theory to examine whether associations between ethnic-identity pride and psychological adjustment (in terms of depression and self-esteem) vary across families and school environments for a sample of 225 Korean American a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…A total of twenty-eight (34.6%, 28/81) studies addressed the relation between depressive symptoms and at least one ascribed indicator [ 32 , 35 , 36 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. Six (7.4%, 6/81) studies examined the correlation between age and depressive symptoms [ 35 , 42 , 43 , 44 , 49 , 54 ]. Of these, four (4.9%, 4/81) studies found that depressive symptoms increased with age [ 35 , 42 , 43 , 54 ], while another found depressive symptoms to decrease with age [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of twenty-eight (34.6%, 28/81) studies addressed the relation between depressive symptoms and at least one ascribed indicator [ 32 , 35 , 36 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. Six (7.4%, 6/81) studies examined the correlation between age and depressive symptoms [ 35 , 42 , 43 , 44 , 49 , 54 ]. Of these, four (4.9%, 4/81) studies found that depressive symptoms increased with age [ 35 , 42 , 43 , 54 ], while another found depressive symptoms to decrease with age [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six (7.4%, 6/81) studies examined the correlation between age and depressive symptoms [ 35 , 42 , 43 , 44 , 49 , 54 ]. Of these, four (4.9%, 4/81) studies found that depressive symptoms increased with age [ 35 , 42 , 43 , 54 ], while another found depressive symptoms to decrease with age [ 44 ]. One study found age to not be associated with depressive symptoms [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations